Ethics and Musical Language: A Gramscian Reading of Dallapiccola’s Liriche greche and Their Influence - Samuel, Jamuna (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2015)
Luigi Dallapiccola (1904–75)—a pioneering figure as serialist, composer of protest music, and trailblazer for the avant-garde—wrote his Greek Lyrics song cycle (1942–5) as an escape from wartime anxiety. I locate the Lyrics within a nexus of technique, text setting, and ethical engagement. That complex resonated with the younger composers Berio, Nono, and Maderna, each responding in the postwar period with settings from the same collection, Quasimodo’s 1940 free translation of classic Greek lyrics. I examine Quasimodo’s ethics, placing his poetry and Dallapiccola’s settings within Gramsci’s notions of language and politics, which were highly influential on postwar Italian composers.